Proceedings 2021 Network and Distributed System Security Symposium 2021
DOI: 10.14722/ndss.2021.24055
|View full text |Cite
|
Sign up to set email alerts
|

CV-Inspector: Towards Automating Detection of Adblock Circumvention

Abstract: The adblocking arms race has escalated over the last few years. An entire new ecosystem of circumvention (CV) services has recently emerged that aims to bypass adblockers by obfuscating site content, making it difficult for adblocking filter lists to distinguish between ads and functional content. In this paper, we investigate recent anti-circumvention efforts by the adblocking community that leverage custom filter lists. In particular, we analyze the anti-circumvention filter list (ACVL), which supports advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…The research community has looked into the filter list curation process to investigate its effectiveness and painpoints [6,47,85,86]. Snyder et al [85] studied EasyList's evolution and showed that it needs to be frequently updated (median update interval of 1.12 hours) because of the dynamic nature of online advertising and efforts from advertisers to evade filter rules.…”
Section: Background and Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The research community has looked into the filter list curation process to investigate its effectiveness and painpoints [6,47,85,86]. Snyder et al [85] studied EasyList's evolution and showed that it needs to be frequently updated (median update interval of 1.12 hours) because of the dynamic nature of online advertising and efforts from advertisers to evade filter rules.…”
Section: Background and Related Workmentioning
confidence: 99%
“…There is, however, optimism in using ML-based approaches to assist with maintenance of filter lists, in a off-line manner. For example, Brave [14], Adblock Plus [66], and the research community [47], have been using ML models to assist FL authors in prioritizing filter rule updates. However, they have two main limitations.…”
Section: Row 3)mentioning
confidence: 99%
See 3 more Smart Citations